KEY COMPETENCES AS THE BASIS OF THE COMPETITIVENESS OF BUSINESS STRUCTURES - SERDYUKOV, Kostyantyn; KORNEYEV, Maxim; KORNIYCHUK, Borys; STAKHIV, Oleksandr; VESNIN, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The concept and features of key competencies are considered. The role of key competencies as the basis of the competitiveness of modern business structures is studied. The relationship between the core competencies of business structures and their ability to provide sustainable competitive advantages in the market is analyzed. The strengths and weaknesses of the key competencies model are considered, which makes it possible to assess its impact on the effectiveness of modern business structures. Foreign and domestic experience in the application of key competencies is analyzed, the importance of their correct definition, strategic use and integration into management processes is emphasized. A model is presented that covers key stages: identification of competencies, assessment of their value for clients of business structures, assessment of the level of competitiveness, formation and distribution of resources, monitoring, control and adjustment of results, assessment of leverage for greater effectiveness of business structures. It is highlighted that key competencies contribute to financial stability, growth of the market value of companies and diversification of markets. The emphasis is on the complexity of implementing the model and the risks of incorrect prioritization. The importance of key competencies in strategic business planning is emphasized, as well as the need for further study of their impact on innovation, growth and long-term competitiveness of modern business structures.
Keywords: competencies; competitiveness; strategic management; system; management; formation; model; business structures